The Effectiveness of Using Think Aloud Strategy on Students’ Reading Achievement in Narrative Text - Fikri, Moh. Hilman; Yasin, Moh. Ilham; Sudrajad, Wahyu; Syakur, Abd.; Azizah, Laila Nur; Iman Jauhari; Gigih Dwi Ananto (International Journal of Sustainable English Language, Education, and Science, 2024)
Think-aloud is one of the transactional strategies that joint process of teachers and students working together to construct understandings of text as they interact with it. The aim of this thesis to investigate that do students who were taught by think aloud strategy has better achievement in the reading narrative text. Toward 23 total students of eight grade of Mts Al-azhar Malang, consist of 11 Males and 12 females of the sample, the researchers conduct the experiment research by distributing 20 pre and post questions of narrative text test. In finding, the mean of total reading test score of 23 students before being taught by using think aloud strategy is (55.43). After getting treatment, the mean score of students’ reading is (71.30). It means that the students’ score is improved. It means that there is significant effect before and after being taught using think aloud strategy toward students reading achievement of narrative text. Based on the result, it can be concluded that think aloud was effective strategy in teaching reading comprehension.